Vivent Health Records: Text Corpus of AV Materials - (:unkn) unknown (My University, 2021)
Founded in 1985 as AIDS Resource Center of Wisconsin, Vivent Health is a national model for providing comprehensive, integrated health and social services to HIV patients. The collection documents the development of Vivent Health from a small provider of limited social services to the largest provider of HIV-health care services in Wisconsin and the most comprehensive AIDS service organization in the United States. This text corpus is derived from the AV materials that are part of the collection. The ARCW digital collection can be found here: https://uwm.edu/lib-collections/arcw/ The full finding aid for the collection can be found here: http://digital.library.wisc.edu/1711.dl/wiarchives.uw-mil-uwmmss0335